PENGATURAN DAN PERTANGGUNGJAWABAN HUKUM TELEMEDICINE DALAM PERSPEKTIF KEPASTIAN HUKUM - Handoko Nugroho Y (2023)
Many countries have responded positively and legalized telemedicine in their countries. This is because telemedicine provides benefits and is a solution for health services that are separated by distance. There is no legal regulation regarding telemedicine health services, this condition can be a source of legal disputes, especially when accompanied by a lack of regulation and legal certainty, the law will be increasingly difficult to enforce. This study uses a normative legal research approach. Legal issues that may arise include licensing, patient privacy and confidentiality of electronic medical records, clinical policies and procedures. Most online applications for healthcare are made by non-medical professionals. The government together with service providers and the public need to establish national standards and guidelines for the use of telemedicine to provide responsible, safe, high quality, fair and non-discriminatory health services. Telemedicine has provided an opportunity to carry out medical practices that are free from distance restrictions, but should not be directed to replace face-to-face interactions between doctors and patients. Until now, there has been no detailed regulation regarding online health services, both in laws and regulations and in the provisions of medical professional ethics. It is time for regulations on telemedicine services to be included in national laws and regulations to meet the needs of technological developments and provide legal certainty for both health practitioners and users of health services. Because there are no health law rules that specifically regulate the provision of telemedicine services, parties who commit violations can be held accountable both civilly, criminally and administratively.